A Study on Radiation Hazard of Granite and Marble Widely Used in Jordan Using Gamma Ray Spectrometer - A. N. Akour; S. Shakhatreh (Atom Indonesia, 2022)
Granite and marble are widely used in building construction, so possible radioactive nuclides inside them may contribute to the exposure dose to human health. The purpose of this study was to investigate the natural radioactivity concentration and assess the radiological risk limits and health care. The samples of marble and granite were pulverized into small, fine, smooth pieces and counted with the GAMMA-X (GMX) spectrometer to measure the radioactivity concentrations of 238U, 232Th, and 40K. The radiological dose, internal and external hazards, and radium equivalent activity were calculated with a standard formula. The results showed that the radioactive concentrations of 238U, 232Th, and 40K in granite were higher than those in marble. The external hazard for granite samples was below unity, while its internal hazard exceeded unity. The radium equivalent activity did not exceed the critical legal level of 370 Bq/kg as a safe level. For marble, the external and internal hazards and radium equivalent activities showed good agreement with the safe construction level. Its external and internal hazards were less than unity, whereas the radium equivalent activities were less than the critical legal level.